Ileal obstruction from Meckel's diverticulum in a neonate: A case report and review of literature - Akputa Aja Obasi; Sebastian O. Ekenze; Uchechukwu Ogbobe (Elsevier, 2015)
Meckel's diverticulum is the most common of the omphalomesenteric duct anomalies encountered in clinical practice. It may present with a wide variety of symptoms. Presentation in the neonatal period is very rare. We present a case of ileal obstruction from Meckel's diverticulum in a neonate with resultant stenosis of the proximal and distal bowel adjoining the Meckel's diverticulum and a short review of literature. Intrinsic intestinal stenosis should be borne in mind as one of the mechanisms by which Meckel's diverticulum causes bowel obstruction.